Tactical Planning in Space Game using Goal-Oriented Action Planning - Restuadi Studiawan; Mochamad Hariadi; Surya Sumpeno (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
Along with improvement of modern electronic games, necessity of an intelligent agent that easily build is needed. One of electronic games that need good intelligent agent is real-time tactics. In this game type, good action planning is necessary to provide best experience to the player. On this paper, we try to find out whether if Goal-Oriented Action Planning (GOAP) is robust enough to be used at tactical game. By using GOAP, tactic dynamism still can be provided with reasonable amount of runtime.Keywords: Artificial intelligence, Games, Goal-Oriented Action Planning, Planning, Unity3D